Leadership, Competence, and Dedication of Christian Education Teachers in the Remote Area of Seko - Yosef Patandung; Selvi Panggua; Adi Sukito; Yong Ho Yoon (Didache: Journal of Christian Education, 2026)
Disparities in the quality and equity of education remain evident in remote areas such as Seko, where teachers perform their professional roles under extreme constraints. This study highlighted the paradox between national demands for teacher professionalism and the reality of challenging geography, limited facilities, and policy inequities faced by teachers in Seko. This research aimed to analyze in depth how teacher leadership contributes to the development and maintenance of competence and dedication amid these limitations, within the framework of inclusive education and educational justice. The study was set in the 3T (tertinggal, terdepan, dan terluar—disadvantaged, frontier, and remote) region of Seko. A qualitative descriptive approach using an action research design was employed. Data was collected through in-depth interviews, field observations, and document analysis. Results: The findings revealed that teachers in Seko adopt transformational, adaptive, and service-oriented leadership styles. Their professional and pedagogical competence was shaped by their adaptability, creativity in utilizing local resources, and strong commitment to delivering culturally relevant learning. Their dedication was reflected in their physical, moral, and spiritual sacrifices. In conclusion, teacher leadership, competence, and dedication were intertwined, forming the foundation of the educational ecosystem in Seko. Teachers function not only as educators but also as social leaders and symbols of resilience, safeguarding educational justice and sustainability in remote areas.